2021
DOI: 10.1063/5.0049509
|View full text |Cite
|
Sign up to set email alerts
|

On the unsteady Reynolds-averaged Navier–Stokes capability of simulating turbulent boundary layers under unsteady adverse pressure gradients

Abstract: Predictive capabilities of unsteady Reynolds-averaged Navier–Stokes (URANS) techniques using the k−ω shear stress transport and Spalart–Allmaras models are assessed for the simulation of turbulent boundary layers under unsteady adverse pressure gradients by comparing their results with direct numerical simulation (DNS) results. Simulations are conducted for separating and reattaching turbulent boundary layers under periodic adverse pressure gradients. Phase-wise comparisons of the velocity, the Reynolds stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
6
8
1
Order By: Relevance
“…We observed that the turbulence models are more accurate for unsteady calculations than for steady ones. On the other hand, Park et al [7] found much worse agreement between RANS solutions and the DNS than observed here. The reason for these two differences most likely lies in the pressuregradient evolution in time.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…We observed that the turbulence models are more accurate for unsteady calculations than for steady ones. On the other hand, Park et al [7] found much worse agreement between RANS solutions and the DNS than observed here. The reason for these two differences most likely lies in the pressuregradient evolution in time.…”
Section: Resultscontrasting
confidence: 87%
“…The results of Park et al [7] are particularly relevant to the present work. They investigated a turbulent flat-plate boundary-layer under unsteady Adverse Pressure Gradients (APGs) to test the performance of the K−ω and SA turbulence models.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…In their very recent investigation, Park, Ha & Donghyun (2021) analysed a TBL under unsteady APGs at a reduced frequency with the aim of testing several turbulence models (, where is the turbulent kinetic energy and the turbulent frequency, and Spalart–Allmaras) and provide insights into their accuracy of predicting unsteady separated flows. The APG was periodically varied to obtain dynamic separation and reattachment but the pressure-gradient distribution was always adverse to favourable and the TSB never disappeared.…”
Section: Introductionmentioning
confidence: 99%
“…However, unfortunately, the RANS-based methods frequently fail to predict highly separated flows, which are dominated by unsteady flow structures with a broad range of scales and, thus, require more complex modeling of the turbulence Reynolds stresses [8]. On the other hand, scale-resolving simulation (SRS) methods, such as large eddy simulation (LES) and hybrid RANS-LES techniques, which are known to be significantly more accurate, are generally deemed to be prohibitively expensive by industrial researchers [9].…”
Section: Introductionmentioning
confidence: 99%